Lipoprotein (a) Screening, and What's Next? - Pasławska Anna; Radom Agnieszka; Tomasik Przemysław (Journal of Cardiovascular Emergencies)
Lipoprotein (a) (Lp(a)) is a low-density lipoprotein (LDL) in which the apolipoprotein B100 molecule is bound to a highly polymorphic, plasminogen-like apolipoprotein (a). The concentration of Lp(a) is predominantly genetically determined, governed by the expression of the LPA gene, and remains relatively stable from early adulthood. The physiological function of Lp(a) is unknown. Lp(a) is recognized as a main carrier of oxidized phospholipids and has strong atherogenic, prothrombotic, and pro-inflammatory properties. Elevated levels of Lp(a) above 75 nmol/l (30 mg/dl) are an independent risk factor for cardiovascular diseases. According to the recommendations of the Polish Lipid Association, Lp(a) should be measured once in a lifetime. This study presents an analysis of the results of Lp(a) screening among adult patients from southeastern Poland (Nowy Sącz county) and evaluates further diagnostic and therapeutic measures for patients with elevated Lp(a) levels. Among the 231 patients screened, 48 individuals (20.8%) had increased Lp(a) levels above 75 nmol/l. Patients with elevated Lp(a) concentration were invited to participate in a survey, in which 31 individuals ultimately took part. Of these, 4 individuals were classified into the moderate risk group, 25 into the high-risk group, and 2 into the very high-risk group for cardiovascular diseases. The pharmacotherapy directly targeting the reduction of Lp(a) is currently undergoing clinical trials. Its effectiveness in decreasing Lp(a) concentrations, along with demonstrating desirable and positive effects on cardiovascular disease outcomes, requires further investigation due to the lack of conclusive evidence. Diet and physical activity have limited impact on Lp(a) concentration. It is recommended to expand preventive programs, including for younger populations, which could help identify patients with genetically determined cardiovascular risk. Additionally, there is a necessity to educate the medical personnel and patients about the significance of Lp(a) and the implementation of guidelines for managing patients with elevated Lp(a) levels.